SUPORTIF DESAIN PADA KLINIK REHABILITASI MENTAL DI JAKARTA - Jovan Adrio; Denny Husin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The saturation level of the COVID-19 pandemic is increasing. Limitation of activities has been carried out five times for approximately a year. The problem is that community productivity reduces with the level of depression increased 69% of the Indonesian population experiencing psychological problems, of which 72% are women and 28% are men. This study aimed to reduce the effects of depression during the pandemic and post-pandemic. The method used in this research is literature study, secondary data collection, case studies from several projects and other research. Mental health disorders cause by limited space for movement, boredom in learning, psychological trauma due to loss of loved ones, and social anxiety. The steps taken in the research are to identify mental health problems that occur in Indonesia, develop a frame of mind, and formulate hypotheses based on literature and case studies.The results of this study are to build clinics and supporting facilities to reduce depression levels by designing facilities for consultations for sufferers and psychologists or psychiatrists, supporting facilities in the form of parks as recreation areas, meditation areas, and support units. There is. These facilities can help patients to overcome the mental illness they are experiencing. Keywords : pandemic; healing; depression; typology; psychology AbstrakTingkat kejenuhan pandemi COVID-19 semakin meningkat. Pembatasan kegiatan yang telah dilakukan sebanyak 5 kali selama kurang lebih selama 1 tahun. Masalahnya produktivitas masyarakat berkurang serta meningkatnya tingkat depresi dengan 69% penduduk Indonesia mengalami masalah psikologis diantaranya 72% adalah wanita dan 28% adalah pria. Tujuan dari penelitian ini adalah untuk mengurangi efek depresi pada saat pandemi dan pascapandemi. Metode yang digunakan pada penelitian ini adalah studi literatur, pengambilan data sekunder, studi kasus dari beberapa proyek dan penelitian lainnya. Gangguan kesehatan mental disebabkan oleh terbatasnya ruang gerak, kejenuhan belajar, trauma psikologis akibat hilangnya orang tersayang, dan kecemasan sosial. Langkah yang diambil dalam penelitian adalah mengidentifikasi masalah kesehatan mental yang terjadi di Indonesia, menyusun kerangka berpikir, dan merumuskan hipotesa berdasarkan studi literatur dan kasus. Hasil dari penelitian ini adalah membangun klinik dan fasilitas penunjang untuk mengurangi tingkat depresi dengan merancang fasilitas untuk konsultasi bagi para penderita dan psikolog atau psikiater, fasilitas penunjang berupa taman sebagai area rekreasi, area meditasi, serta unit pendukung. Terdapat. Dengan fasilitas tersebut dapat membantu pasien untuk mengatasi penyakit mental yang dialaminya.